PERANCANGAN WEBSITE PROFIL TOKO DAN KATALOG PRODUK DI ALFANET COMPUTER - Rahayu, Syifaa Puspita; Bastian , Ade (Universitas Majalengka, 2025)
This practical work report discusses the design and implementation of a company profile website and product catalog for Alfanet Computer. The main objective of this project is to create an online platform that provides complete and structured information about the store, product specifications, availability, and prices. The research was conducted using the Waterfall development method, starting from requirements analysis, system design with UML, implementation using HTML, CSS, JavaScript, and PHP, to testing through the black-box method. The website enables store owners to manage product data efficiently and allows customers to access product information anytime and anywhere without visiting the store. The results of this project show that the developed website successfully displays store profiles and product catalogs in a more systematic and user-friendly manner. This system is expected to help Alfanet Computer improve service quality and support business development by expanding access to information through digital media.